Pedagogies of care in performative schools. Issue 1 (2nd January 2020) - Dadvand, Babak; Cuervo, Hernan
ABSTRACT: With growing policy pressures on schools to produce outcomes, there are concerns about the loss of caring relationships from education. In this article, we argue that rather than eliminating all forms of care, neoliberal reform agendas have co-opted the practices of care by encouraging an ethic of care that serves instrumental agendas of student achievement and performance. Drawing upon semi-structured interview data from a teacher and a principal in a school located in a low socio-economic suburb of Melbourne, we assert that such a care ethic often works to the detriment of socially marginalized young people. This is because schools' caring practices driven by performative agendas fail to respond to the more complex relational needs of some students. The mismatch between the caring intentions of the institution and the actual needs of the students leads to relational tension paving the way for the breakdown of the caring relationships.